PF.48 Prenatal Diagnosis of Moderate and Severe Cerebral Ventriculomegaly – Our Experience an a Single Tertiary Referral Centre. (26th April 2013) - Monteith, C; Flood, K; Jaleel, S; Hayes, B; Barry, C; Geary, M; Malone, FD
Abstract : The diagnosis of fetuses with cerebral ventriculomegaly >1.2 mm prenatally is challenging due the number of possible etiologies and variable prognoses. Recommended investigations include ultrasonographic assessment, TORCH screening, MRI evaluation along with specialised paediatric postnatal follow-up. There is limited data about the antenatal course and obstetric outcomes of affected pregnancies managed expectantly. We sought to evaluate all cases of prenatally diagnosed moderate to severe ventriculomegaly managed in our centre. We performed a retrospective cohort study of patients attending/referred to the Rotunda FAU from 2006–2011. Cases were identified from the FAU database and included for evaluation if ultrasonographic measurements >1.2 mm in either/both cerebral ventricles were documented.  During this six year period, there were 71 cases identified that met study criteria with pregnancy outcome data available for 65 cases. Of these 83.1% (54/65) elected to continue the pregnancy following diagnosis with 44/54 continuing their care in the Rotunda Hospital. The mean gestation at time of ultrasonographic diagnosis was 24 + 3 weeks (14 + 4 – 39 + 4). Other prenatal investigations performed included 23 amniocenteses, 17 TORCH screens and 12 fetal MRIs. Vaginal delivery was achieved in 33.3% of women (n = 13) (mean HC 325.9 mm) with the remaining 66.7% (n = 26) undergoing caesarean section (mean HC 347.9 mm).  The majority of cases with ventriculomegaly >12 mm were managed expectantly within our unit. We found that this finding had a significant impact on the mode of delivery. Overall less than 50% cases had a definitive aetiology prior to delivery which highlights importance of thorough paediatric follow-up postnatally.